Convergence report 2012 (Luxembourg, 2012)
"Convergence Reports examine whether Member States satisfy the conditions for adopting the single currency. Convergence reports are issued by the European Commission and the European Central Bank every two years, or more often if a country intending to join the euro requests it. These reports form the basis for the decision on whether a Member State may join the euro area.